Drug dealing in Rincón Grande of Pavas: acceptance and opposition of the local population - Saborío, Sebastián (2023)
To understand if the authority of drug dealing groups is considered legitimate by the local population of Rincon Grande de Pavas, a set of impoverished neighborhoods of capital of Costa Rica, the author carried out research between March 2019 and March 2020. During the field work the author realized 67 in deep interviews, mainly with residents of the analyzed area. The results show that drug dealing groups are not considered legitims by the residents, mainly because they do not offer them concrete benefits and impose their rules in an authoritative way by using violence.